Peran Dukungan Keluarga, Strategi Koping, dan Ketahahan Diri sebagai Pendukung Motivasi untuk Pulih pada Narapidana Rehabilitasi Narkoba: Sistematik Reviu - Suseno, Akbar; Susanti, Herni; Panjaitan, Ria Utami (Poltekkes Kemenkes Kendari, 2023)
The current phenomenon of narcotics and dangerous substance abuse (hereinafter referred to as drugs) is increasingly worrying, which is reflected in the increasing number of narcotics prisoners. Prisoner life requires family support, self-resilience and coping strategies to grow motivation to recover from narcotics abuse. This research aims to analyze the role of family support, coping strategies, resilience with recovery motivation in prisoners who are drug rehabilitation. The research method used is a systematic review through searching for articles adapted to the formulation of research questions using the PICO formula in the ProQuest, Sage Journal, ScienceDirect, Scopus and google scholar databases. The articles reviewed with the inclusion criteria and the articles were published between 2016 and 2023. The search results found 13 articles with research show that there is a significant relationship between family support, coping strategies, resilience and recovery motivation in prisoners who are drug rehabilitation. In conclusion, the recovery motivation from prisoners who are drug rehabilitation is influenced by family support, coping strategies and resilience.